Analysis Of Differences In The Adequacy Of Breast Milk Production In Hormonal Family Planning Acceptors - Lestari, Aldina; Nabila (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2017)
According to Basic Health Research data (2013), the use of family planning for the national figure has increased from 55.8% (2010) to 59.7% (2013). Hormonal contraception users (84.57%) and non hormonal (19.35%). Where the coverage of exclusive breastfeeding in Indonesia in 2015 is only (55.7%). The factors that affect milk production are the use of contraceptives.The purpose of this study is to know the difference in the adequacy of breast milk production in hormonal family planning acceptors in the working area of ​​Caile Health Center, Ujung Bulu District, Bulukumba Regency.This study uses an observational analytic design with a